The developmentalist discourse and the subaltern struggle within the framework of the Mayan Train - Morales Cardoso, Armando Nicolás (2025)
This work analyzes the discourse of the Mexican State on development for the implementation of the Mayan Train (TM) megaproject, which contains a neo-colonial and modernity process, but, in the end, it comes to implement the rationalist process ofcapital. in the region. Likewise, it is reviewed how through the implementation of this policy agency was achieved within the subaltern struggle of the Regional Indigenous and Popular Council of Xpujil S.C. The Council, through legal struggle, obtained thecancellation of the project on its territory. However, the project continues in execution despite the protection achieved.